Pengaruh Suku Bunga, Nilai Tukar Mata Uang, Harga Emas Dunia, dan Indeks Dow Jones terhadap Harga Saham Perusahaan Properti dan Real Estat dengan Inflasi sebagai Variabel Moderasi - Hasanudin Hasanudin; Anugrah Kumaruza (FOCUS, 2020)
The purpose of this research is to study the effect of interest rates, rupiah currency exchange rates, world gold prices, and the Dow Jones Index on stock prices of property and real estate companies with inflation as a moderating variable. This study uses a case study of 4 stocks, namely BSDE, CTRA, PWON, and SMRA with the research data period January 2014-December 2019. The analysis was carried out using the ARCH / GARCH model using the Eviews 10 application. The results showed that there were quite varied results regarding patterns of the relationship between the independent variables on the four stock prices studied. The most notable difference is in the PWON stock